2002
DOI: 10.1191/0960327102ht212oa
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to low-level chemicals and ionizing radiation: reactive oxygen species and cellular pathways

Abstract: Reactive oxygen species (ROS), which contribute to the energy landscapes in and around cells, play numerous roles in maintaining normal cell homeostasis as components of signaling pathways. Excessively high levels of ROS, on the other hand, can lead to pronounced DNA damage and a variety of cellular responses, including cell cycle arrests, senescence, apoptosis and possibly cancer. Far less is known, however, about how supra-basal levels of ROS that can be generated in response to low doses of ionizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 18 publications
1
50
1
1
Order By: Relevance
“…4c) and NAC (data not shown) in HSC-5 cells. H2AX, a histone variant, is phosphorylated in response to ROSmediated DNA damage (Lehnert and Iyer 2002;Rogakou et al 1998). We conWrmed that arsenic-induced phosphorylation of H2AX, H2AX (lanes 1 and 2 in Fig.…”
Section: Barium Inhibited Arsenic-mediated Apoptosis Through Suppressmentioning
confidence: 85%
“…4c) and NAC (data not shown) in HSC-5 cells. H2AX, a histone variant, is phosphorylated in response to ROSmediated DNA damage (Lehnert and Iyer 2002;Rogakou et al 1998). We conWrmed that arsenic-induced phosphorylation of H2AX, H2AX (lanes 1 and 2 in Fig.…”
Section: Barium Inhibited Arsenic-mediated Apoptosis Through Suppressmentioning
confidence: 85%
“…One possible mechanism underlying these effects is generation of reactive oxygen species ROS, which at low levels induces cell proliferation and at high levels induces cell death through DNA damage [14]. To determine whether DBD plasma treatment of cells induced DNA damage, we looked at phosphorylation of H2AX, a histone variant that is phosphorylated in response to DNA double strand breaks [15].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, low-level ionizing radiation has been shown to stimulate the cell proliferation, 15) or it may be that free electrons induce reduction reactions in the cells. It is also reported that carbon materials such as graphite and activated charcoal can cause the proliferation of certain bacteria over a distance of several centimeters.…”
Section: Discussionmentioning
confidence: 99%